The study of efficient and effectiveness of IIUM campus shuttle bus service - Olabayonle, Oladejo Aliu (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Increasing motorisation and its resultant effects such as congestion, parking problem and pollution have underscored the need for a shift towards the use of more sustainable modes of transport such as public transport. Worsening traffic congestion and air quality have been associated with the proliferation of usage of private vehicles in most university environment, of which the International Islamic University Malaysia (IIUM) is no exception. It is recognised that shuttle buses hold the promise of relieving the growing congestion of our campuses if they are managed efficiently and sustainably. For this purpose, this study extends the exploration of the IIUM Shuttle Campus Service, using a quantitative traffic engineering measure known as the Level of Service standards or LOS and passengers' level of satisfaction and descriptive analysis for the riders' level of satisfaction, travel time and passenger ridership. Three performance measures, namely fixed-route hour of service, fixed-route service frequency and passenger-load threshold, were evaluated to determine the existence and extent of such performance of service. A Passenger satisfaction and preference survey was conducted to complement some qualitative explanations left void by the LOS evaluation. Methods of on-board face-to-face intercept survey and adoption of Global Positioning System (GPS) was deployed in the collection of primary data. More than 370 survey forms were distributed, but after collection and data cleaning, only a total of 363 were analysed. Findings of the study supported and confirmed the efficiency and effectiveness of services provision, show that most riders (72.5%) were female and undergraduate students (62.5%) and they used the shuttle bus for class purpose mostly (73.8%), traveling with it usually one or two times daily (67.2%). Also, majority of the riders were dissatisfied with the punctuality, waiting time, travel time and the service frequency of the shuttle bus with (81.3%, 84.6%, 68.6% and 84.3%) respectively. The study thus recommends in the both short term and long term, management should increase the service frequency of the shuttle bus, install transit information board, provision of new vehicles where necessary and introduction of right of way. The findings from this study can be used as a benchmark for bus service improvement programmes for future public transportation system.